THE IMPORTANCE OF REPLACEMENT VALUE. - Schmidt, Fritz (The Accounting Review, 1930)
Abstract This article shows that replacement costs furnish the best basis for producing serviceable financial statements to use for current managerial purposes or for use in planning mergers and reorganizations where the status of an enterprise as a whole is under consideration. The concept of profit sought is one which will enable the enterprise to function property as an economic unit in all economic situations. It must be that profit which at the moment of its calculation can actually be distributed-that profit which gives a value-picture in the profit and loss statement corresponding to the current economic situation. The profit of an undertaking can only consist of what is produced above the maintenance of business assets. A sharp line is drawn by this definition between assets and profits. Profits are also found in differences in time-values. While the entrepreneur can measure the degree of his success in buying and selling if the sale of his goods brings him returns which would permit him to buy or produce an additional quantity of the same goods at the moment of selling, the purpose of the speculator is differently orientated.